Báo cáo đánh giá tác động chính sách dự án Luật Quản lý, bảo vệ công trình quốc phòng và khu quân sự - Bộ Quốc phòng (2023)
Toàn văn Báo cáo đánh giá tác động chính sách dự án Luật Quản lý, bảo vệ công trình quốc phòng và khu quân sự.